The Sister of Telemachus: The Main Character of Margaret Cavendish’s “Assaulted and Pursued Chastity” as the Embodiment of Progress and Conventions - Kvéder, Bence Gábor (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Margaret Cavendish’s (1623–1673) “Assaulted and Pursued Chastity” (1656) is one of the English writer’s early prose works. However, the text already displays a kind of formal experimentation and playfulness, as well as many of the extraordinary and subversive ideas the Duchess’ mature literary voice of the 1660s is characterized by. Accordingly, it deals with topics such as travelling, marriage, military conflicts, colonization, as well as the concept of virtue and the risks of virtuous behaviour. The protagonist of the story is often analyzed as an early manifestation or prototype of the active, resourceful, travelling female individual: Travellia’s wit, determination, oratory and argumentation skills indeed seem to predict the lasting success of Cavendish’s later heroines, and even the full potential of their writer’s creative powers. In my paper, I intend to take a look at how the main character’s progressive and, to a certain extent, even masculine traits and deeds are juxtaposed with her ultimate decision to adhere to the cultural conventions of femininity by getting married, focusing mainly on the various ways in which this kind of shift and the ensuing double perspective of the heroine might influence the reading and overall evaluation of “Assaulted and Pursued Chastity.”